STRATEGI AMERIKA SERIKAT MEMBENDUNG PENGARUH REPUBLIK RAKYAT TIONGKOK DI KAWASAN LAUT CINA SELATAN PADA MASA PEMERINTAHAN PRESIDEN DONALD TRUMP - Muhammad Nizar Hamdi Nasution; Umi Oktyari Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
People's Republic of China in the South China Sea Region. After China's claims and military infiltration on islands in the South China Sea, it has created tension from several countries in the region, including the United States. The United States began implementing a series of strategies to stem China's hegemony in the South China Sea, which has the ambition to become a global power country. The method used in this research is a qualitative research method. This qualitative research method has characteristics that understand, explain and describe the state of a fact. Data were taken from book documents, national and international scientific journals, official publications, and the internet. The results of this study indicate that the United States during the Trump Administration was influenced by several factors in making policies. The writer sees this based on the foreign policy theory of James N. Rosenau which the writer uses. The United States carried out a series of policies to stem China's influence starting from the political, economic, diplomatic and military dimensions. The United States conducted a series of agreements and negotiations related to military assistance and development in several countries around the region through the Free and Open Indo-Pacific (FOIP) policy. On the military side, the United States sent its navy to conduct a series of navigation operations around islands claimed by China in the South China Sea. Keywords: South China Sea, America, China, Containment